Progress in etiological diagnosis of viral meningitis - Xu, Hongyan; Chen, Peng; Guo, Shihan; Shen, Xiaokai; Lu, Yun (Frontiers in Neurology, 2023)
In recent years, with the rapid development of molecular biology techniques such as polymerase chain reaction and molecular biochip, the etiological diagnosis of viral encephalitis has a very big step forward. At present, the etiological examination of viral meningitis mainly includes virus isolation, serological detection and molecular biological nucleic acid detection. This article reviews the progress in etiological diagnosis of viral meningitis.